PERBANDINGAN TINDAK ILOKUSI DALAM TUTURAN KOMENTATOR SEPAK BOLA LIGA INGGRIS DAN LIGA INDONESIA: KAJIAN PRAGMATIK LINTAS BUDAYA: Ilocutionary Act in The Speech of The Indonesian League and English League Football Spectator: A Cross-cultural Pragmatic Study - Salimulloh Tegar Sanubarianto; Sri Yanuarsih; I Wayan Letreng; M. Imron Abadi (TOTOBUANG, 2023)
Abstract This study aims to compare the speeches of football commentators in the English and Indonesian Leagues through a pragmatic theory of cross-cultural. The researcher chooses the English Premier League as the subject of comparison to the Indonesian League due to the FIFA datum, Premier League is the football league with the most spectators in the world. The researcher observes the illocutionary acts that appear in the speeches of the commentators between the two leagues. The researcher used a documentative data collection method. The researcher transcribed the video as the data source and analyzed it using Searle's speech act theory. The results showed that the types of illocutionary acts in both data were the same, assertive, expressive, and declarative . It's just that the difference appears at the level of detail function. The Indonesian League commentator's speech has more specific function. Apart from that, the speeches of Indonesian League football commentators were dominantly expressive speeches praising (31.15%), while for English League commentators were assertive in informing (41.05%). A comparison of the two cross-cultural commentators' speech data can reflect the speech habits of each community.Keywords: illocutionary acts, football commentators, cross-cultural pragmatics Â  Abstrak Penelitian ini bertujuan untuk membandingkan tuturan komentator sepak bola Liga Inggris dan Liga Indonesia dalam kajian pragmatik lintas budaya. Liga Inggris dipilih sebagai subjek pembanding Liga Indonesia karena sesuai data FIFA Liga Inggris adalah liga sepak bola dengan penonton paling banyak di dunia. Penelitian ini mengamati tindak ilokusi yang muncul pada tuturan komentator dua liga tersebut. Metode pengumpulan data dilakukan secara dokumentatif. Peneliti melakukan transkripsi terhadap video sumber data kemudian menganalisisnya dengan teori tindak tutur Searle. Hasil penelitian menunjukkan tipe tindak ilokusi yang muncul pada kedua data ternyata sama, yaitu tipe asertif, ekspresif, dan deklaratif. Hanya saja, perbedaan muncul pada tingkat detail fungsi. Tuturan komentator Liga Indonesia memiliki detail fungsi lebih banyak. Selain itu, yang dominan muncul dalam tuturan komentator sepak bola Liga Indonesia adalah tuturan ekspresif memuji (31,15%), sedangkan untuk tuturan komentator Liga Inggris adalah asertif menginfomasikan (41,05%). Perbandingan dua data tuturan komentator lintas budaya ini mampu merefleksikan kebiasaan tutur masing- masing masyarakatnya. Kata Kunci: tindak ilokusi, komentator sepak bola, pragmatik lintas budaya